Performance of low-cost GNSS equipment in monitoring of horizontal displacements - Oku Topal, Gueldane; Karabulut, Mustafa Fahri; Aykut, Nedim Onur; Akpinar, Burak (TAYLOR & FRANCIS LTD, 2023)
To investigate theperformance of low-cost GNSS equipment in monitoring horizontal displacements ANN-MB-GNSS and A10 antenna were installed on Zeiss-BRT-006 reduktionstachymeter, which can move with mm sensitivity in the horizontal plane. Ten days of static data were recorded with U-Blox-ZED-F9P-02B-GNSS receiver and processed with CSRS-PPP online-service. Considering theobservation period(12,6,3,1h), nine horizontal displacement magnitude tests were performed.Inaddition, GNSS-PPPAR solution percentages, multipath and signal-to-noise ratio values were considered. The results reveal that 20mm displacement can be determined (6mmRMSE) using the PPP approach based on a 3-hour observation period with A10antenna and 30mm can be determined (15mmRMSE) with UBX antenna with a 6-hour observation.
Keywords: Low-cost GNSS; low-cost antenna; PPP; displacement monitoring; GPS; SIMULATION; RESOLUTION; PRECISION; SERVICES; VELOCITY; RECEIVER; Engineering; Geology; Remote Sensing